KARAKTERISTIK WIRAUSAHA, MODAL USAHA DAN STRATEGI PEMASARAN TERHADAP PERKEMBANGAN UMKM - Liantifa, Melifia (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The formulation of the problem in this study is how influence of entrepreneurial characteristics,venture capital and marketing strategy on the development of MSMEs in Ambai village?. The objectives of this study are (1) to determine the effect of entrepreneurial characteristics on the development of MSMEs in Ambai village partially. (2) To find out the effect of venture capital on the development of MSMEs in Ambai village partially. (3) To find out the effect of marketing strategy on the development of MSMEs in Ambai village partially. (4) To determine the effect of entrepreneurial characteristics, business capital and marketing strategies on the development of MSMEs in Ambai Village simultaneously? The analysis used in this research is descriptive quantitative with multiple linear regression approach. The results of the study explain that there is a significant positive influence between entrepreneurial characteristics, business capital, and marketing strategy on the development of MSMEs Ambai Village partially, while simultaneously there is a significant positive influence between entrepreneurial characteristics, business capital, and marketing strategies on the development of Ambai Village MSMEs. The magnitude of the influence between entrepreneurial characteristics, business capital, and marketing strategy on the development of MSMEs in Ambai Village is 99.1%.